Chain of Responsibility in Land Transportation Associated with Overloading Activities - Dea Safira Setiono; Hilda Yunita Sabrie (Fakultas Hukum Universitas Lampung, 2023)
Heavy vehicles are one of the modes of land transportation in Indonesia in the activity of transporting goods. A large number of transport companies creates business competition related to the supply of freight costs. To get more profit, transportation companies practice over dimension and overloading. Overloading which is more prevalent in transportation, causes losses for various groups. One of the losses can impact workers in a transportation company where the liability for the crew of the vehicle is not regulated in detail. The existence of the principle of Chain of Responsibility in regulations regarding the transportation of heavy vehicles aims to expand the responsibility for losses incurred, such as overloading practices. This principle ensures that all subjects in the logistics chain have the duty to ensure compliance with regulations, including truck owners, transportation operators, goods senders, and goods recipients. This study discusses the responsibility of the parties in the delivery of goods related to overloading and recognizes the concept of Chain of Responsibility in transportation by land in overloading practices. The research method used is empirical juridical with a conceptual approach and a statute approach. For these problems, this study aims to analyze the accountability of the parties in overloading activities and to recognize the concept of Chain of Responsibility in land transportation in overloading practices.